ANALYSIS OF PHYTO-CONSTITUENTS, ANTIOXIDANT, AND ALPHA AMYLASE INHIBITORY ACTIVITIES OF PERSEA AMERICANA MILL., RHODODENDRON ARBORETUM SM. RUBUS ELLIPTICUS SM. FROM ARGHAKHANCHI DISTRICT NEPAL - Subba, Bimala; Gaire, Sanjay; Raj Sharma, Khaga (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: To evaluate the phytochemical, antioxidant activities, and Î±-amylase inhibition assay for methanolic extract of three ethnomedicinal plants, namely Persea americana Mill., Rubus ellipticus Sm., and Rhododendron arboretum Sm. collected from Arghakhanchi District of Nepal using in vitro studies. Methods: Methanolic plant extracts were prepared by cold percolation method. Analysis of phytochemical constituents was carried out using standard methods. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was used to evaluate in vitro antioxidants activities. Furthermore, inhibition effect of extracts on Î±- amylase enzyme was carried out by using starch as a substrate, pancreatic Î±-amylase as the enzyme, and acarbose as standard. Results: Phytochemical screening of methanolic extract of all three selected plants displayed the presence of different chemical constituents such as alkaloids, polyphenols, flavonoids, terpenoids, saponins, glycosides, and tannins. The results of DPPH assay revealed that R. ellipticus and R. arboreum were most active with half maximal inhibitory concentration (IC50) values 33.41 Î¼g/ml and 47.28 Î¼g/ml, respectively. R. ellipticus was found to be effective toward Î±-amylase inhibition with IC50 values 269.94 Î¼g/ml. Conclusion: The preliminary results of this study have put forward R. ellipticus into promising herbs with good antioxidant activities and Î±-amylase inhibition potential although further studies are needed to assess its mechanism of action.